Genetic testing and blood biomarkers in paediatric pulmonary hypertension. Expert consensus statement on the diagnosis and treatment of paediatric pulmonary hypertension. The European Paediatric Pulmonary Vascular Disease Network, endorsed by ISHLT and DGPK. (6th April 2016) - Pattathu, Joseph; Gorenflo, Matthias; Hilgendorff, Anne; Koskenvuo, Juha W; Apitz, Christian; Hansmann, Georg; Alastalo, Tero-Pekka
Abstract : Childhood-onset pulmonary arterial hypertension (PAH) is considered complex and multifactorial, with relatively poor estimates of the natural history of the disease. Strategies allowing earlier detection, establishment of disease aetiology together with more accurate and sensitive biomarkers could enable better estimates of prognosis and individualise therapeutic strategies. Evidence is accumulating that genetic defects play an important role in the pathogenesis of idiopathic and hereditary forms of PAH. Altogether nine genes have been reported so far to be associated with childhood onset PAH suggesting that comprehensive multigene diagnostics can be useful in the assessment. Identification of disease-causing mutations allows estimates of prognosis and forms the most effective way for risk stratification in the family. In addition to genetic determinants the analysis of blood biomarkers are increasingly used in clinical practice to evaluate disease severity and treatment responses. As in genetic diagnostics, a multiplex approach can be helpful, as a single biomarker for PAH is unlikely to meet all requirements. This consensus statement reviews the current evidence for the use of genetic diagnostics and use of blood biomarkers in the assessment of paediatric patients with PAH.